THE INFLUENCE OF WORK-FAMILY CONFLICT ON EMPLOYEE PERFORMANCE WITH WORK-LIFE BALANCE AS AN INTERVENING VARIABLE - Permatasari, Diah Hesti; Ratnawati, Intan (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
Work-family conflict is a role conflict that arises between employees, on the one hand they have to work in the office, on the other hand they have to take care of the entire family, so it is difficult to differentiate between conflicts between work and family and between family and work. Work-family conflict is a conflict between work and family roles faced by employees. In this research, the population was determined, namely employees at the BUMN Bank PT The sampling technique in this research is a purposive sampling technique, meaning that not all samples can be used in the research. Purposive sampling technique is a sampling technique with certain criteria in research. The criteria were all female employees at the State-Owned Bank PT In sampling this research, the author used the Saturated sample formula, namely sampling if the entire population is used as a sample and is also known as a census. The research results found Work Family Conflict has a negative and insignificant effect on employee performance for employees of BUMN PT X Semarang City.Work Family Conflict has a positive and significant effect on Work Life Balance for employees of BUMN PT X Semarang City Work Family Conflict has a positive and significant effect on employee performance for employees of BUMN PT X Semarang City. This means that a high level of Work Family Conflict does not have a greater influence on Work Life Balance. Based on the test results using the SmartPLS application program version 3.2.9 (Smart Partial Least Square), it can be concluded that the indirect influence on the research model consists of the indirect influence on the Work Family Conflict variable on Employee Performance through Work Life Balance. Keywords: Work Family Conflict, Work Life Balance, Employee Performance